Cox proportional hazards regression modeling an illustration - Dadole, Noverose B.; Dumanjug-Tagbac, Charlotte F. (2014)
The purpose of this study is to expose the Cox regression modeling. Cox proportional hazards regression builds a predictive model for time-to-event date. It will yield an equation for the hazard or the probability of the occurence of event as a function of several explanatory variables. The data used is actual marriage data. The method used for parameter estimation is based on proportional hazards assumption and the diagnostic checking is based on residuals. The statistical software used is R, and the methods of the analysis in R, are prsented in this paper. Finally, the model that best fits to the data include an interaction term which verifies all the diagnostic checking.
Keywords: Statistics; Mathematical models